Jinhaku Sonans skipper type collection deposited at Taiwan Agricultural Research Institute (Lepidoptera: Hesperiidae) - Chiba, Hideyuki; Hsu, Yu-Feng; Tsukiyama, Hiroshi; Lo, Philip Yik-Fui; Chen, Chien-Ren; Wang, Shou-Ming (Zootaxa, 2009)
Of the 12 skipper taxa described by Jinhaku Sonan (1892-1984) from Taiwan and Hainan Island, 2 are recognized as valid species-level names, 4 as valid subspecies-level names, whereas the remaining 6 are considered junior subjective synonyms of other taxa. A revised status is established for a Hainan taxon, Tagiades japetus hainana Sonan, stat. rev., and Polytremis kiraizana (Sonan) is formally confirmed as a species endemic to Taiwan. The valid species-level names are Ochlodes niitakanus (Sonan) and Polytremis kiraizana (Sonan). The valid subspecies-level names are Lobocla bifasciata kodairai Sonan, Pseudocoladenia dan sadakoe Sonan & Mitono, Notocrypta feisthamelii arisana Sonan, and Tagiades japetus hainana Sonan. Tagiades menaka kotoshona Sonan is considered a junior subjective synonym of T. trebellius martinus Plötz, Ampittia maro matsumurai Sonan a junior subjective synonym of Ampittia dioscorides etura Mabille, Parnara kotoshona Sonan a junior subjective synonym of Parnara guttata (Bremer & Grey), Parnara ranrunna Sonan a junior subjective synonym of Caltoris cahira austeni (Moore), Gangara thyrsis hainana Sonan a junior subjective synonym of Gangara thyrsis thyrsis (Fabricius), and Telicota palmarum hainanum Sonan a junior subjective synonym of Cephrenes acalle oceanica (Mabille) in the present study.